Histochemical Study of Non-Specific Esterases Motor Unit of the Rabbit - R.AL- Salihi, A.; T. AL-Azzawi, H.; M. Al-Khateeb, H. (The Iraqi Journal of Veterinary Medicine, 1990)
The distribution of alpha naphthyl asetrase and naphthol AS-D acetate esterase was studied in the motor neurons of the ventral horn of the spinal cord segments L4, L5, and SI, supplying the extensor digitorum longus musscle (EDL) of the rabbit together with the peripheral nerve supplying EDL and the muscle itself. Strong activity was demonstrated in the motor neurons, in schwann cells and in the axons of peripheral nerve bundlds. Abundant reaction was located in the motor end-plates of muscle fibres making them easily recognizable. biological interpretation of esterases was discussed